The impact of public information awareness and service towards public engagement - Zellatifanny, Cut Medika; Rumata, Vience Mutiara; Sakinah, Awit Marwati (Jurnal Studi Komunikasi, 2021)
Public participation in policymaking remains a significant challenge in Indonesia. Previous studies found that public participation in the policymaking process is still dominated by the elite (i.e. policymakers). This paper argues that a lack of well-informed public causes diminishing public involvement in policymaking. This study aims to fill the gap in public participation study in Indonesia, particularly the impact of public information on public participation. This study measures to what extent public information awareness and public information service may form public participation behaviour. As quantitative research, this study uses a survey as the primary method to collect data. The questionnaire was constructed through concepts and legal documents related to public information disclosure and public information services. The multi-stage proportional random sampling is applied with the number of samples in this study is 1,584 in 25 provinces (out of 34 provinces). The results show that public information awareness significantly impacts public participation, while public information service satisfaction does not affect public participation.